2019
DOI: 10.1071/sr18337
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness and longevity of the urease inhibitor N-(2-nitrophenyl) phosphoric triamide (2-NPT) with N-(n-butyl) thiophosphoric triamide (nBTPT) in reducing ammonia emissions from cattle urine applied to dairy-grazed pasture soils

Abstract: The objective of this laboratory incubation study was to assess the effectiveness and longevity of urease inhibitor N-(2-nitrophenyl) phosphoric triamide (2-NPT), along with the commonly used N-(n-butyl) thiophosphoric triamide (nBTPT), in reducing ammonia (NH3) emissions from cattle urine applied to pasture soils. It was hypothesised that 2-NPT would be effective as a longer-lasting inhibitor to reduce emissions after the deposition of urine during multiple grazing events. Two dairy-grazed pasture soils (Fluv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…While rapid leaching was unlikely in this low permeability soil, it is clear that at least some urea-N had moved into layers below the fertilizer band by 21 DAF. The relative immobility of banded NBPT in soils of high-clay and OM content has been recently identified by Janke (2020) and is likely a dominant factor in the rapid 'loss-of-function' observed in this and other studies (Watson et al 1994;Adhikari et al 2019). Soluble urea-N may diffuse and/ or move with mass flow, creating an asynchrony of inhibitor and substrate location that reduces the effectiveness of NBPT.…”
Section: Urease Inhibitors Have Limited Impact In Banded Applicationssupporting
confidence: 52%
“…While rapid leaching was unlikely in this low permeability soil, it is clear that at least some urea-N had moved into layers below the fertilizer band by 21 DAF. The relative immobility of banded NBPT in soils of high-clay and OM content has been recently identified by Janke (2020) and is likely a dominant factor in the rapid 'loss-of-function' observed in this and other studies (Watson et al 1994;Adhikari et al 2019). Soluble urea-N may diffuse and/ or move with mass flow, creating an asynchrony of inhibitor and substrate location that reduces the effectiveness of NBPT.…”
Section: Urease Inhibitors Have Limited Impact In Banded Applicationssupporting
confidence: 52%
“…The application of NPT has been shown to lower NH3 volatilization by 89% after 19 days of incubation [39], and depending on the soil characteristics, it also has greater longevity than NBPT [40]; therefore, the inhibitory effect of 2-NPT may last longer than that of NBPT. However, currently, 2-NPT is still on a laboratory-scale production; therefore, it is not easily available in the market and for field purposes.…”
Section: Urease Inhibitorsmentioning
confidence: 99%
“…-N) in floodwater, soil pH, and temperature (Liu et al 2007;Tian et al 2001). A recent study by Adhikari et al (2019) observed high pH buffering capacity of soil with higher organic matter content and vice versa, suggesting influence of organic matter on NH 3 emissions. Thus, investigation of the behavior of NH 3 volatilization under different environmental conditions is vital to increase N use efficiency and to reduce the environmental pollution specially for paddy fields conditions (Liu et al 2015).…”
mentioning
confidence: 92%